Fundamental Study of Marine Resource Conservation Wisdom for Traditional Fishermen - Erman Syarif (Universitas Negeri Makassar, 2021)
Marine resources in Indonesia are experiencing degradation. Conservation based on local wisdom is a very valuable asset in conserving marine resources in Indonesia. This research aims to identify: (1) what are the characteristics of traditional fishermen in Bajoe Village, and (2) what are the forms of local wisdom in marine resource conservation. This type of research is qualitative. The research location is in Bajoe Village, Tanete Riattang Timur District, Bone Regency, South Sulawesi Province. Sources of data are informants (Ponggawa Fishermen, Ponggawa Nelayan Bugis and Sawi-sawi Fishermen, Community Leaders, and Village Heads). Data was collected by observation, interviews, literature review and documentation. Data analysis techniques are data collection, data reduction, data presentation, and data conclusion drawing. The results of the research show that: (1) the fishing communities in Bajoe Village generally live on the beach in an elongated and grouped pattern and depend on marine products for their livelihood. (2) forms of local wisdom, namely: a) values, b) norms, c) knowledge, and f) technology. Therefore, a revitalization program, refunctionalization of local wisdom, and socialization to the public are needed. Local wisdom is a very valuable asset so that it can be used as reference material in making policies related to marine resource conservation efforts in Indonesia, especially in South Sulawesi.